2014
DOI: 10.1002/cne.23647
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor but not vesicular zinc promotes TrkB activation within mossy fibers of mouse hippocampus in vivo

Abstract: The neurotrophin receptor, TrkB receptor tyrosine kinase, is critical to central nervous system (CNS) function in health and disease. Elucidating the ligands mediating TrkB activation in vivo will provide insights into its diverse roles in the CNS. The canonical ligand for TrkB is brain-derived neurotrophic factor (BDNF). A diversity of stimuli also can activate TrkB in the absence of BDNF, a mechanism termed transactivation. Zinc, a divalent cation packaged in synaptic vesicles along with glutamate in axons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 50 publications
(108 reference statements)
3
21
3
Order By: Relevance
“…Hence, although BDNF may be upregulated throughout the forebrain, its specific pattern of expression may differ between brain regions. Although the precise mechanism for BDNF upregulation in ZnT3 null mice is unknown, this finding is consistent with the report by Helgager that showed increased BDNF levels in relatively young ZnT3 null brains26. The combination of upregulated BDNF and increased brain size in male ZnT3 null mice suggests the interesting possibility that BDNF upregulation is one of the factors that causes large brains as well as autism phenotypes in these mice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, although BDNF may be upregulated throughout the forebrain, its specific pattern of expression may differ between brain regions. Although the precise mechanism for BDNF upregulation in ZnT3 null mice is unknown, this finding is consistent with the report by Helgager that showed increased BDNF levels in relatively young ZnT3 null brains26. The combination of upregulated BDNF and increased brain size in male ZnT3 null mice suggests the interesting possibility that BDNF upregulation is one of the factors that causes large brains as well as autism phenotypes in these mice.…”
Section: Discussionsupporting
confidence: 91%
“…Because mammalian brains contain a large and dynamic pool of zinc in glutamatergic synaptic vesicles (synaptic zinc), it is plausible that synaptic zinc plays a role in MMP activation and BDNF upregulation around synapses. However, contrary to our expectations, a recent study by Helgager demonstrated that ZnT3 null mice, in which synaptic zinc is absent, show increased levels of BDNF26. Hence, the absence of synaptic zinc, especially during brain development, may cause the upregulation of BDNF by an unidentified mechanism and may possibly induce large brain size and autistic phenotypes.…”
contrasting
confidence: 99%
“…The BDNF levels measured by ELISA were somewhat low relative to levels described in previous reports (e.g., see Helgager et al, 2014). This could be due to methodological aspects of the sample preparation.…”
Section: Bdnf Protein Levelscontrasting
confidence: 70%
“…For certain experiments, samples were acidified during preparation to increase the detection of BDNF (Okragly & Haak-Frendscho, 1997). The acidification procedure was adapted from Helgager et al (2014) and was performed after the samples spent 1 h on ice, but prior to centrifugation. The pH of the samples was adjusted to <3.0 using 1 M HCl, and the samples were left for 20 min at room temperature.…”
Section: Sample Collection and Protein Extractionmentioning
confidence: 99%
See 1 more Smart Citation